Faktor-Faktor Yang Mempengaruhi Manajemen Laba (Studi Empiris Pada Perusahaan Manufaktur Yang Terdaftar di BEI Periode Tahun 2008-2011) - Dani Rahman Raja; Rita Anugerah; Pipin Kurnia (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2014)
Earnings management is defined as a managerial discretionary practice of timing strategic and operating decisions (e.g., accelerating sales, postponing research and development) or choosing accrual estimates (excessive reserves) to manage short-term earnings. Earnings management is made possible and is often legitimately accomplished within the flexibility of GAAP rather than through noncompliance with GAAP. Earnings management with the purpose of creating misleading financial information or misrepresenting financial performance can constitute fraud. This study aimed to assess the effect of institutional ownership, independent board, percentage of public shares, audit committee, and leverage on earnings management. The population in this research that companies listed on the indonesia stock exchange (BEI) period 2008-2011. Sampling was purposive sampling method. Data collection method is a method of documentation. Hypothesis testing using linear regression analysis.Keywords : institutional ownership, independent board, percentage of public shares, audit committee, leverage, and earnings management.